1999
DOI: 10.1073/pnas.96.12.6763
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct forms of the 64,000 M r protein of the cleavage stimulation factor are expressed in mouse male germ cells

Abstract: Polyadenylation in male germ cells differs from that in somatic cells. Many germ cell mRNAs do not contain the canonical AAUAAA in their 3 ends but are efficiently polyadenylated. To determine whether the 64,000 M r protein of the cleavage stimulation factor (CstF-64) is altered in male germ cells, we examined its expression in mouse testis. In addition to the 64,000 M r form, we found a related Ϸ70,000 M r protein that is abundant in testis, at low levels in brain, and undetectable in all other tissues examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
158
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(174 citation statements)
references
References 99 publications
(67 reference statements)
14
158
2
Order By: Relevance
“…‡ Micrometer per second Ϯ SD. for spermatogenesis and male fertility because of its expression during male meiosis when CstF-64 is absent (5). In support of this hypothesis, Cstf2t Ϫ/Ϫ males were infertile due to low sperm counts (Table 3), significant developmental defects in spermiogenesis (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…‡ Micrometer per second Ϯ SD. for spermatogenesis and male fertility because of its expression during male meiosis when CstF-64 is absent (5). In support of this hypothesis, Cstf2t Ϫ/Ϫ males were infertile due to low sperm counts (Table 3), significant developmental defects in spermiogenesis (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Although polyadenylation is nearly universal, features of polyadenylation are different in mammalian male germ cells than in other tissues: male germ cell mRNAs exhibit increased alternative polyadenylation (3,4), decreased use of the AAUAAA polyadenylation signal (5,6), and reduced dependence on downstream sequence elements (DSEs) (7). These differences suggest a modified mechanism for polyadenylation in male germ cells.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Model for tissue-specific su(f) autoregulation+ The Su(f) protein regulates its own level by promoting the utilization of poly(A) site in su(f) intron 4, which leads to the formation of a truncated transcript+ In dividing tissues, this autoregulation is weak, possibly because of the lack or the low amount of another component essential for Su(f) activity on the su(f) intronic poly(A) site+ This allows Su(f) accumulation+ In nondividing tissues, su(f) autoregulation is strong, possibly as a result of a high level of the protein required for efficient Su(f) activity on the su(f) intronic poly(A) site+ This results in the synthesis of a very low level of Su(f) protein+ type expression pattern of the P[su(f)-lacZ]G reporter is restored in the su(f) ts67g mutant+ Therefore, in that experiment, accumulation of the Su(f)-b-galactosidase protein is repressed in nondividing tissues but not in dividing tissues although the Su(f) protein is present at the same level in both tissues+ This suggests that this repression in nondividing tissues depends on another protein that stimulates utilization of the poly(A) site in intron 4 (Fig+ 5)+ This protein would induce a modification of Su(f) activity either via a direct posttranslational modification of Su(f) or by interacting with Su(f)+ Such a Su(f)-interacting protein could be a specific protein or a component of the general 39-end processing machinery+ An obvious candidate is the 64K subunit of CstF known to interact with the 77K subunit in human (Takagaki & Manley, 1994)+ Variations in the level of this 64K subunit contribute to the shift in poly(A) site selection in the immunoglobulin M heavy-chain locus, during B cell differentiation (Takagaki et al+, 1996;Takagaki & Manley, 1998)+ Autoregulation of su(f) appears to be conserved in another Drosophila species, D. virilis , as the structure of the su(f) gene as well as sequences downstream of the intronic poly(A) site, including the GU-rich motif, are conserved in this species+ Interestingly, such autoregulation has been proposed to occur for the yeast homolog of su(f), the RNA14 gene (Mandart, 1998)+ The RNA14 gene also produces truncated RNAs, whose accumulation requires wildtype RNA14 function+ The fact that autoregulation of this gene is conserved from yeast to Drosophila suggests that the level of this protein must be tightly regulated+ Consistent with this, overexpression of su(f) in Drosophila using the UAS/Gal4 system can lead to lethality+ In mammals, several examples document the fact that variations in the general cleavage factor CstF participate in the regulation of poly(A) site choice+ In most cases, the 64K subunit of CstF has been found to be responsible for these variations+ Variations in the activity of 64K have been reported to occur during the shift in poly(A) site choice in adenovirus (Mann et al+, 1993)+ An increase in the 64K level participates in the switch of poly(A) site utilization in the immunoglobulin M heavy-chain locus during B cell maturation (Takagaki et al+, 1996;Takagaki & Manley, 1998)+ The 64K subunit level has also been shown to increase in cultured cells induced to proliferate (Martincic et al+, 1998), and recently a new form of the 64K protein has been described in mouse (Wallace et al+, 1999); this form is specific to testis and brain and has been proposed to replace the 64K form during some steps of spermatogenesi...…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in male germ cells and may have important roles in germ-cell-specific polyadenylation and spermatogenesis [144][145][146][147][148].…”
Section: Cstf-64 (Rna15p)mentioning
confidence: 99%